Heat-latent cationic polymerization initiator, curable resin composition, and metal joined body

By using Lewis acid-type cationic polymer compound in the resin composition to control its activation state under humid and heat conditions, the problem of discoloring metals in the existing heat-sensitive resin composition is solved, and high-quality maintenance of resin and metals is achieved.

JP2025066056APending Publication Date: 2025-04-22NIPPON SHOKUBAI CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024151308
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-03-07
Filing Date
2024-09-03
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The conventional thermosensitive resin compositions tend to discolor the contact metal parts under humid and heat conditions, resulting in deterioration of the properties of the metal and insulating failure.

Method used

Using a thermosensitive cationic polymer compound containing a Lewis acid-type cationic polymer compound, the activation of the polymer is controlled by adjusting the temperature to ensure that the polymer is inactivated at room temperature and can effectively catalyze the polymerization of the resin when heated.

Benefits of technology

It is achieved to suppress the color change of resin and metal under humid and heat conditions, maintain the high-quality characteristics of the resin, and avoid insulation failure and performance degradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025066056000027
    Figure 2025066056000027
  • Figure 2025066056000001
    Figure 2025066056000001
  • Figure 2025066056000002
    Figure 2025066056000002
Patent Text Reader

Abstract

To provide a cationic polymerization initiator which is heat-latent and can control start of polymerization of a compound having a cationic curable functional group by adjustment of a temperature, a heat-latent cationic polymerizable resin composition containing the cationic polymerization initiator, and a metal-clad laminate in which discoloration of an insulation layer and a metal layer is suppressed under moist heat condition is suppressed.SOLUTION: A heat-latent cationic polymerization initiator contains a specific Lewis acid type cationic polymerization initiator and an amine compound, wherein parts of the Lewis acid type cationic polymerization initiator and the amine compound form a complex, the remainder of the amine compound exists while being separated from the Lewis acid type cationic polymerization initiator, and a molar ratio of an amino group contained in the free amine compound to 1 mol of a boron atom contained in the Lewis acid type cationic polymerization initiator is 0.15 or more and 1.70 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cationic polymerization initiator that is thermally latent and capable of controlling the initiation of polymerization of a compound having a cationic curable functional group by adjusting the temperature, a curable resin composition containing the cationic polymerization initiator, and a bonded body of a cured body and a metal in which discoloration of the cured body and the metal under moist and hot conditions is suppressed. [Background technology]

[0002] Thermosetting epoxy resins are widely used in electronic products such as printed circuit boards, memory, and CPUs due to their high electrical insulation, water resistance, and chemical resistance. In addition, due to their high corrosion resistance, they are also used as an ingredient in anti-corrosion paints for automobiles and ships. They are also used for painting the inside of beverage cans. They are also used as industrial adhesives, and in the construction field as structural adhesives for concrete and steel plates. Recently, they have also been used as adhesives for lightweight, high-strength high-performance materials such as carbon fiber and glass fiber.

[0003] Epoxy monomers are polymerized by cationic polymerization. Compared to radical polymerization, cationic polymerization has the advantage that curing inhibition by oxygen does not occur and shrinkage during curing is small. However, if polymerization starts immediately after mixing the epoxy monomer and the cationic polymerization initiator, there is a risk that the product will harden before it is used.

[0004] Therefore, the research group of the present inventors has developed a thermally latent polymerization initiator composition that contains tris(pentafluorophenyl)borane, a cationic polymerization initiator, and a specific amine compound, does not initiate polymerization at room temperature, but initiates polymerization at a lower temperature, and has excellent catalytic ability (Patent Document 1). In addition, the research group has developed a curable resin composition that contains a cationic curable compound having a cyclic ether group, a cationic curable compound having a double bond, and a specific boron compound, and that has excellent storage stability and can give a cured product with high transparency and uniformity with good productivity (Patent Document 2). Furthermore, the research group has developed a polymerization initiator composition that contains a triaryl boron compound and a cyclic ether compound (Patent Document 3).

[0005] In addition, a thermosetting epoxy resin composition is known that contains an epoxy resin, a specific aromatic amine compound, a specific boron-phosphorus complex, and a specific phosphorus compound and can form a cured film with excellent voltage resistance, adhesion, and heat resistance in a short curing time (Patent Document 4). In addition, Patent Document 5 discloses a curing catalyst that contains a Lewis acid and a monoamine or a heterocyclic aromatic organic compound. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2012 / 036164 Brochure [Patent Document 2] JP 2014-152194 A [Patent Document 3] JP 2019-218267 A [Patent Document 4] Patent Publication No. 2021-66890 [Patent Document 5] Special Publication No. 2008-544067 Summary of the Invention [Problem to be solved by the invention]

[0007] As described above, thermally latent resin compositions that begin to cure when heated are known. However, the present inventors have found that some cured products of thermally latent resin compositions discolor the contact area with metal or the surrounding metal parts under moist and hot conditions. The discolored metal parts undergo deterioration of characteristics and corrosion, causing insulation failure. Therefore, an object of the present invention is to provide a cationic polymerization initiator that is thermally latent and capable of controlling the initiation of polymerization of a compound having a cationic curable functional group by adjusting the temperature, a thermally latent cationic polymerizable resin composition containing the cationic polymerization initiator, and a metal-clad laminate in which discoloration of the insulating layer and metal layer under moist and hot conditions is suppressed. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to solve the above problems, and as a result, have found that in a composition containing a complex of a Lewis acid-type cationic polymerization initiator and an amine compound, the proportion of a free amine compound that does not form a complex is also important for the corrosion resistance of a cured product or metal, and have completed the present invention. The present invention will now be described.

[0009] [1] A method for producing an ink-jet printer comprising the steps of: the Lewis acid type cationic polymerization initiator and a part of the amine compound form a complex, the remainder of the amine compound is present free from the Lewis acid cationic polymerization initiator, A thermally latent cationic polymerization initiator, characterized in that the molar ratio of amino groups contained in the free amine compound to 1 mole of boron atoms contained in the Lewis acid type cationic polymerization initiator is 0.15 or more and 1.70 or less.

[0010] [ka]

[0011] [In the formula, F represents a fluoro group; R 1 represents a hydrocarbon group which may have a substituent, l is an integer of 1 to 5, m is an integer of 1 to 3, n is an integer of 0 to 2, m+n=3, If n is 2, then two R 1 may be the same or different.] [2] The thermal latent cationic polymerization initiator according to the above [1], further comprising a solvent. [3] The thermal latent cationic polymerization initiator according to the above [1] or [2], wherein the amine compound is a hindered amine compound. [4] The thermal latent cationic polymerization initiator according to [1] or [2], wherein the amine compound is an imidazole compound and a hindered amine compound. [5] The thermally latent cationic polymerization initiator according to any one of the above [1] to [4], wherein the Lewis acid type cationic polymerization initiator represented by the formula (I) is tris(pentafluorophenyl)borane. [6] A curable resin composition comprising a compound having a cationically curable functional group and the thermal latent cationic polymerization initiator according to any one of [1] to [5] above. [7] The curable resin composition according to [6], wherein the compound having a cationically curable functional group is at least one selected from the group consisting of an alicyclic epoxy compound, a hydrogenated epoxy compound, an aromatic epoxy compound, and an oxetane compound. [8] A cured product of the curable resin composition according to [6] above, and a metal, A bonded body, characterized in that the cured product and the metal are in contact with each other. [9] A printed wiring board comprising an insulating layer containing a cured product of the curable resin composition according to [6] above, and a conductor layer on one or both sides of the insulating layer.

[0012]

[10] A method for producing a cured product, comprising: A step of preparing a curable resin composition by mixing a compound having a cationic curable functional group and a thermal latent cationic polymerization initiator; The method includes a step of curing the curable resin composition by heating, the thermal latent cationic polymerization initiator contains a Lewis acid type cationic polymerization initiator represented by formula (I) and an amine compound, the Lewis acid type cationic polymerization initiator and a part of the amine compound form a complex, the remainder of the amine compound is present free from the Lewis acid cationic polymerization initiator, The production method is characterized in that the molar ratio of amino groups contained in the free amine compound to 1 mole of boron atoms contained in the Lewis acid type cationic polymerization initiator is 0.15 or more and 1.70 or less.

[11] The method according to

[10] , wherein the thermal latent cationic polymerization initiator further contains a solvent.

[12] The method according to

[11] above, wherein the solvent is an ether solvent having a boiling point of 80°C or higher and 160°C or lower.

[13] The method according to any one of the above

[10] to

[12] , wherein the heating temperature of the curable resin composition is 80° C. or higher and 160° C. or lower.

[14] The method according to any one of the above

[10] to

[13] , wherein the cationically curable functional group is an epoxy group and / or an oxetanyl group.

[15] The method according to any one of the above

[10] to

[14] , wherein the compound having a cationically curable functional group is one or more compounds selected from the group consisting of alicyclic epoxy compounds, aromatic epoxy compounds, and oxetane compounds.

[16] The method according to any one of the above

[10] to

[15] , further comprising a step of molding the curable resin composition.

[17] The method according to

[16] , wherein the curable resin composition is molded by a spin coating method, a solvent casting method, a dipping method, a spray coating method, or a dispenser method.

[0013]

[18] A cured product of a curable resin composition containing the Lewis acid type cationic polymerization initiator represented by the formula (I), an amine compound, and a bisphenol epoxy compound represented by the following formula (III): [ka] [In the formula, R 21 and R 22 are independently H, C 1-6 Alkyl groups, halogenated C 1-6 R represents an alkyl group or a phenyl group. 21 and R 22 Let's get together and 3-10 may form a cycloalkyl group, r is an integer between 0 and 100.

[19] The cured product according to

[18] , further comprising rubber particles.

[20] The cured product according to

[18] or

[19] above, having a loss factor tan δ of 0.01 or more at 40°C. Effect of the Invention

[0014] The polymerizable resin composition according to the present invention exhibits excellent thermal latency, probably because the Lewis acid type cationic polymerization initiator liberated by heating can catalyze the polymerization reaction of a compound having a cationic curable functional group. Therefore, the curable resin composition containing the thermally latent cationic polymerization initiator according to the present invention does not cure at room temperature, but starts curing by heating, so that it is possible to control the curing by adjusting the temperature. Furthermore, the cured product of the curable resin composition according to the present invention is not easily discolored even under moist and hot conditions, and the metal in contact with it is also not easily discolored, so that it is useful, for example, as a component of the insulating layer of a metal-clad laminate in contact with a metal. In addition, the cured product produced by the present invention is suppressed from defects such as coloring and cracking. Therefore, the present invention is industrially very excellent as a curable resin composition that can not only control curing but also has excellent quality after curing. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a photograph showing the appearance of the cured products of Examples 1 and 2 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The thermal latent cationic polymerization initiator according to the present invention contains the Lewis acid type cationic polymerization initiator represented by the formula (I). Hereinafter, the "compound represented by formula (x)" will be abbreviated as "compound (x)".

[0017] Thermal latent polymerization initiators are mainly divided into protonic acid type and Lewis acid type. Protonic acid type produces a strong acid as a by-product by reaction with a compound having a cationic curable functional group, whereas Lewis acid type does not produce a strong acid as a by-product. Furthermore, the ligand coordinated to the Lewis acid type cationic polymerization initiator functions as a stabilizer for the generated resin.

[0018] In the formula (I), examples of the hydrocarbon group include C 1-6 Alkyl group, C 2-6 Alkenyl groups, and C 2-6 Examples of the aliphatic hydrocarbon group include an aliphatic hydrocarbon group selected from the group consisting of alkynyl groups and C 1-6 Examples of the alkyl group include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, s-butyl, t-butyl, n-pentyl, and n-hexyl. 1-4 is an alkyl group, more preferably C 1-2 C is an alkyl group, and even more preferably methyl. 2-6 Examples of alkenyl groups include ethenyl (vinyl), 1-propenyl, 2-propenyl (allyl), isopropenyl, 2-butenyl, 3-butenyl, isobutenyl, pentenyl, hexenyl, and the like. 2-4 alkenyl group, more preferably ethenyl (vinyl) or 2-propenyl (allyl). 2-6 Examples of the alkynyl group include ethynyl, 1-propynyl, 2-propynyl, 2-butynyl, 3-butynyl, pentynyl, and hexynyl. 2-4It is an alkynyl group, more preferably ethynyl or propynyl.

[0019] Examples of the substituent that the hydrocarbon group may have include, for example, C 1-6 Examples of the substituents include one or more selected from an alkoxy group, a halogeno group, a cyano group (-CN) and a nitro group (-NO2).

[0020] C 1-6 The alkoxy group refers to a linear or branched saturated aliphatic hydrocarbon oxy group having 1 to 6 carbon atoms. Examples of the alkoxy group include methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, t-butoxy, n-pentoxy, and n-hexoxy. 1-4 is an alkoxy group, more preferably C 1-2 It is an alkoxy group, and even more preferably it is methoxy.

[0021] Examples of the halogeno group include fluoro, chloro, bromo and iodo, with chloro or bromo being preferred, and chloro being more preferred.

[0022] The number of substituents in the hydrocarbon group is not particularly limited as long as it is substitutable, and can be, for example, from 1 to 8. The number is preferably 6 or less or 4 or less, more preferably 3 or less or 2 or less, and even more preferably 1.

[0023] The number l of fluoro groups on the phenyl group is preferably 2 or more, or 3 or more, more preferably 4 or more, and even more preferably 5.

[0024] The number m of phenyl groups is preferably 2 or more, and more preferably 3.

[0025] As the Lewis acid type cationic polymerization initiator, for example, tris(pentafluorophenyl)borane is preferable.

[0026] The amine compound according to the present invention refers to an organic compound having an amino group, but also includes ammonia (NH3). That is, the amine compound according to the present invention is classified into ammonia, a primary amine compound, a secondary amine compound, and a tertiary amine compound. In the present invention, the nitrogen atom of the amine compound is coordinated with the boron atom of the Lewis acid cationic initiator (I) to suppress the catalytic activity of the Lewis acid cationic initiator (I), but the catalytic activity of the Lewis acid cationic initiator (I) is expressed by dissociating both of them by heating. That is, the amine compound imparts thermal latency to the Lewis acid cationic initiator (I).

[0027] The primary amine compound is a compound (RNH2) in which one of the hydrogen atoms of ammonia is replaced with a hydrocarbon residue. 1 ) is an example of a compound represented by the formula: [ka] [In the formula, R 2 is C 1-6 represents an alkyl group, p represents an integer of 0 to 5, q is an integer of 1 to 6, p+q≦6, When p is an integer of 2 or more, R 2 may be the same or different.]

[0028] A secondary amine compound is a compound (R2NH) in which two hydrogen atoms of ammonia are replaced by a hydrocarbon residue or the like, and a tertiary amine compound is a compound (NR3) in which three hydrogen atoms of ammonia are replaced by a hydrocarbon residue or the like. Examples of secondary amine compounds and tertiary amine compounds include those represented by the following formula (II 2 ) is a compound having a piperidine structure represented by the formula: [ka] [In the formula, X represents an ether group (-O-) or a single bond. R 3 ~R 7 are independently H or C 1-6 represents an alkyl group.

[0029] Examples of the secondary amine compound and the tertiary amine compound include those represented by the following formula (II 3 ) or (II 4 ) is an example of a compound represented by the formula: [ka] [In the formula, X and R 3 ~R 7 has the same meaning as above, Y represents a linker group or a single bond; R 8 , H, C 1-6 An alkyl group, or the piperidine structure (II 2 ).

[0030] The linker group is the piperidine structure (II 2 ) or to facilitate the synthesis of the compound. There are no particular limitations on the type of compound that exhibits such an effect. For example, C 1-10 Examples of the linked group include an alkanediyl group, an ether group (-O-), a thioether group (-S-), a carbonyl group (-C(=O)-), a thionyl group (-C(=S)-), an ester group (-OC(=O)- or -C(=O)-O-), an amide group (-NH-C(=O)- or -C(=O)-NH-), a urea group (-NH-C(=O)-NH-), and a thiourea group (-NH-C(=S)-NH-); and a group in which 2 or more and 5 or less of these groups are linked together. Examples of the linked group include a C alkyl group having a group selected from the group consisting of an ether group, a thioether group, a carbonyl group, a thionyl group, an ester group, an amide group, a urea group, and a thiourea group at one or both ends. 1-10 Mention may be made of alkanediyl groups.

[0031] [ka] [In the formula, R 9 ~R 12 At least one of the piperidine structures (II 2 ) and the rest is C 1-20 represents an alkyl group.

[0032] The amine compound is preferably a hindered amine compound. A hindered amine compound is an amine compound in which the nucleophilicity of the lone electron pair of the nitrogen atom is weakened by steric hindrance due to a substituent. For example, R 4 ~R 6 All are C 1-6 Piperidine structure (II) 2 ) is an amine compound having the formula:

[0033] Examples of the hindered amine compound include the following compounds. [ka]

[0034] [ka]

[0035] The amine compound may be an imidazole compound represented by the following formula: [ka] [In the formula, R 13 ~R 16 are independently a hydrogen atom (-H) or C 1-6 represents an alkyl group. In imidazole compounds, R 16 is preferably a hydrogen atom.

[0036] In amine compounds, C 1-6The alkyl group refers to a linear or branched monovalent saturated aliphatic hydrocarbon group having 1 to 6 carbon atoms. Examples include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, s-butyl, t-butyl, n-pentyl, and n-hexyl. 1-4 is an alkyl group, more preferably C 1-2 It is an alkyl group, most preferably methyl.

[0037] The amine compound may be used alone or in a mixture of two or more kinds. The mixture may be a mixture of amine compounds that differ only in the number of carbon atoms in the alkyl group, or may be a mixture of different kinds of amine compounds. The number of amine compounds in the mixture is preferably 10 or less, more preferably 8 or less or 5 or less, and even more preferably 2. An example of the mixture of amine compounds is a mixture of a hindered amine compound and an imidazole compound.

[0038] The ratio of the two types of amine compounds may be appropriately adjusted depending on the thermal latent curing property, corrosion resistance, etc. For example, the molar ratio of the hindered amino group to the non-hindered amino group may be 1 or more and 10 or less. The molar ratio is preferably 2 or more or 3 or more, and more preferably 8 or less or 5 or less.

[0039] The thermal latent cationic polymerization initiator according to the present invention may contain a solvent. If the initiator contains a solvent, it becomes easy to mix with a compound having a cationic curable functional group, and the initiator is highly convenient. On the other hand, the initiator may not contain a solvent from the viewpoint of storage stability.

[0040] The solvent is not particularly limited as long as it can adequately dissolve the Lewis acid type cationic polymerization initiator (I), the amine compound, and their complexes. Examples of the solvent include alcohol solvents such as methanol, ethanol, and 2-propanol; ether solvents such as dimethyl ether, ethyl methyl ether, tetrahydrofuran, dioxane, and methoxycyclopentane; ketone solvents such as acetone and ethyl methyl ketone; ester solvents such as ethyl acetate and γ-butyrolactone; Examples of suitable solvents include aliphatic hydrocarbon solvents such as n-pentane, n-hexane, cyclohexane, and methylcyclohexane; aromatic hydrocarbon solvents such as benzene and toluene; halogenated hydrocarbon solvents such as dichloroethane, chloroform, carbon tetrachloride, and chlorobenzene; and mixed solvents of these. Of these, ether solvents are preferred.

[0041] The solvent preferably has a boiling point of 80° C. or more and 160° C. or less. If the boiling point is 80° C. or more, the curable resin composition can be sufficiently heated, and the curable resin composition can be sufficiently cured. If the boiling point is 160° C. or less, it is possible to prevent the curable resin composition from being excessively heated. As the solvent, an ether-based solvent having a boiling point of 80° C. or more and 160° C. or less is particularly preferred, and an ether-based solvent having a boiling point of 90° C. or more and 120° C. or less is more preferred. In addition, an ether-based solvent having a boiling point of 90° C. or more and 110° C. or less is even more preferred in that it can satisfactorily form a cured product such as a cured film having no cracks and a uniform thickness.

[0042] When the thermal latent cationic polymerization initiator according to the present invention contains a solvent, the concentration may be appropriately adjusted. For example, the total concentration of the Lewis acid type cationic polymerization initiator (I) and the amine compound can be adjusted to 10 mass% or more and 80 mass% or less, and preferably 25 mass% or more and 50 mass% or less.

[0043] Neutral three-coordinate boron compounds are called boranes and exhibit electron accepting properties, and amine compounds have a lone pair of electrons on the nitrogen atom, so it is believed that the Lewis acid cationic polymerization initiator (I) and the amine compound form a complex. However, the present inventors have found that even if the Lewis acid cationic polymerization initiator (I) and the amine compound are mixed so that the molar ratio of the boron atom to the nitrogen atom is 1:1, the two compounds do not necessarily form a complex with the exact amount, which is believed to depend mainly on the structure of the amine compound.

[0044] The present inventors have also found that by reacting a sufficient amount of an amine compound with the Lewis acid type cationic polymerization initiator (I) in a quantity sufficient to form a complex with the Lewis acid type cationic polymerization initiator (I) and allowing a specific ratio of a free amine compound to be present relative to the Lewis acid type cationic polymerization initiator (I), not only is thermal latency imparted to the Lewis acid type cationic polymerization initiator (I), but also a metal corrosion inhibitory effect is exhibited.

[0045] In addition to forming a complex with the Lewis acid type cationic polymerization initiator (I), the free amine compound present in a free state from the Lewis acid type cationic polymerization initiator (I) may be present alone in the thermal latent cationic polymerization initiator, or may form, for example, a salt with another anion.

[0046] Specifically, in a solvent, an amine compound is reacted with the Lewis acid cationic polymerization initiator (I) so that the amino group in the amine compound is more than 1 mole, thereby forming a complex between the Lewis acid cationic polymerization initiator (I) and the amine compound, and adjusting the molar ratio of the amino group contained in the free amine compound to 1 mole of boron atoms contained in the Lewis acid cationic polymerization initiator to 0.15 or more and 1.70 or less. If the molar ratio is 0.15 or more, the thermosetting property is more reliably exhibited. On the other hand, if the molar ratio is 1.70 or less, even if the cured product made by the thermal latent cationic polymerization initiator is in contact with a metal, corrosion of the cured product itself and the metal can be suppressed. The molar ratio is preferably 0.25 or more, more preferably 0.30 or more, and more preferably 1.50 or less, more preferably 1.00 or less.

[0047] In the present disclosure, the "residual amine compound" refers to the amine compounds contained in the thermal latent cationic polymerization initiator other than the amine compound that forms a complex between the Lewis acid type cationic polymerization initiator and the amine compound. That is, the "residual amine compound" is present in the thermal latent cationic polymerization initiator as a free amine compound, independent of the thermal latent cationic polymerization initiator and the complex.

[0048] In the narrow sense, the amino group may refer to an -NH group; however, in the present disclosure, the amino group is broadly defined to include not only an -NH group, but also an -NH- group in a secondary amine compound, an >N- group in a tertiary amine compound, and, when ammonia is used as the amine compound, ammonia itself.

[0049] Since the amine compound that forms a complex with the Lewis acid type cationic polymerization initiator (I) loses its basicity, the concentration and amount of the free amine compound that is liberated from the Lewis acid type cationic polymerization initiator can be measured by acid titration of the thermal latent cationic polymerization initiator. The concentration and amount of the free amine compound is measured in accordance with the second method of 3. Amine value measurement method (2) of the Quasi-drug Raw Materials Standards 2006. Specifically, the thermal latent cationic polymerization initiator and bromophenol blue are dissolved in ethanol, and titrated with 0.5 mol / L hydrochloric acid until the solution turns green. From the amount and concentration of the acid added, the amount of the free amine compound contained in the thermal latent cationic polymerization initiator is calculated, and the molar ratio of the amino group contained in the free amine compound to 1 mole of boron atom contained in the Lewis acid type cationic polymerization initiator is calculated.

[0050] The thermally latent cationic polymerization initiator according to the present invention can be easily produced by simply mixing the Lewis acid cationic polymerization initiator (I) and the amine compound in a solvent. For example, the Lewis acid cationic polymerization initiator (I) and the amine compound may be mixed in a solvent at room temperature, more specifically, at 10°C or higher and 40°C or lower. After mixing the Lewis acid cationic polymerization initiator (I) and the amine compound, the solvent may be distilled off. Post-reaction treatment may be carried out according to a conventional method.

[0051] The curable resin composition according to the present invention contains the above-mentioned thermal latent cationic polymerization initiator and a compound having a cationic curable functional group. The compound having a cationic curable functional group attacks a cation generated from the thermal latent cationic polymerization initiator to generate a cation, which then attacks the cation generated by another cationic curable functional group, thereby polymerizing.

[0052] Examples of the cationically curable functional group include a carbon-carbon double bond group and a cyclic ether group, such as a vinyl group, an epoxy group, and an oxetanyl group.

[0053] Examples of compounds having a cationically curable functional group include aliphatic unsaturated hydrocarbons, aromatic compounds having a vinyl group, and cationically curable heteroatom-containing compounds.

[0054] Examples of the aliphatic unsaturated hydrocarbon include C 1-butene, 2-butene, isobutene, 1-pentene, 3-methyl-1-butene, 1-hexene, 2-hexene, 3-methyl-1-pentene, 2,3-dimethyl-1-butene, 3,3-dimethyl-1-butene, vinylcyclopentane, 3,3-dimethyl-1-pentene, vinylcyclohexane, 1-octene, 2-octene, 2,4,4-trimethyl-1-pentene, vinylnorbornane, 1-decene, camphene, α-pinene, β-pinene, vinyladamantane, and the like. 1-12 Aliphatic unsaturated hydrocarbon compounds: C having two or more vinyl groups, such as butadiene, 1,4-pentadiene, cyclopentadiene, 1,5-hexadiene, 1,3-cyclohexadiene, 2,5-norbornadiene, dicyclopentadiene, 4-vinyl-cyclohexene, 5-vinyl-2-norbornene, 5-ethylidene-2-norbornene, etc. 1-12 Aliphatic unsaturated hydrocarbon compounds are included.

[0055] Examples of aromatic compounds that constitute aromatic compounds having a vinyl group include phenyl, naphthyl, anthryl, phenanthryl, pyrenyl, and the like. 6-18Examples of aromatic compounds include aromatic compounds having one vinyl group, such as styrene, α-methylstyrene, 3-methylstyrene, 4-methylstyrene, 3-ethylstyrene, 4-ethylstyrene, 3-propylstyrene, 4-isopropylstyrene, 3-butylstyrene, 4-tert-butylstyrene, 4-hexylstyrene, 4-octylstyrene, 3-(2-ethylhexyl)styrene, 4-(2-ethylhexyl)styrene, 2,4-diphenyl-4-methyl-1-pentene, 1-vinylnaphthalene, 2-vinylnaphthalene, 2-isopropenylnaphthalene, 9-vinylanthracene, and 1-vinylanthracene. 6-18 Aromatic compounds: C having two or more vinyl groups, such as 1,3-divinylbenzene, 1,4-divinylbenzene, 1,3-diisopropenylbenzene, 1,4-diisopropenylbenzene, 1,4-divinylnaphthalene, 1,5-divinylnaphthalene, 1,4-diisopropenylnaphthalene, 9,10-divinylanthracene, allylstyrene, isopropenylstyrene, butenylstyrene, and octenylstyrene. 6-18 Examples of such compounds include aromatic compounds.

[0056] The cationic curable heteroatom-containing compound refers to a compound that contains a cationic curable functional group containing a heteroatom, such as an epoxy group or an oxetanyl group, and is polymerized by cations. Examples of cationic curable heteroatom-containing compounds having an epoxy group include epoxy resins having a cyclohexane skeleton, alicyclic epoxy resins, aliphatic epoxy resins, and aromatic epoxy compounds.

[0057] An example of an epoxy resin having a cyclohexane skeleton is a 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol.

[0058] Examples of alicyclic epoxy resins include vinylcyclohexene monoxide, 1,2-epoxy-4-vinylcyclohexane, 1,2:8,9 diepoxy limonene, 3,4-epoxycyclohexenylmethyl-3',4'-epoxycyclohexene carboxylate, 3,4-epoxycyclohexenylmethyl-3',4'-epoxycyclohexene carboxylate, and hydrogenated epoxy compounds.

[0059] Examples of the hydrogenated epoxy compound include hydrogenated bisphenol A type epoxy compounds, hydrogenated bisphenol F type epoxy compounds, hydrogenated bisphenol E type epoxy compounds, diglycidyl ethers of hydrogenated bisphenol A type alkylene oxide adducts, diglycidyl ethers of hydrogenated bisphenol F type alkylene oxide adducts, hydrogenated phenol novolac epoxy compounds, and hydrogenated cresol novolac epoxy compounds.

[0060] Examples of aliphatic epoxy resins include ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, trimethylolpropane diglycidyl ether, and polyethylene glycol diglycidyl ether.

[0061] Examples of aromatic epoxy compounds include aromatic bisphenol A type epoxy compounds, aromatic bisphenol F type epoxy compounds, aromatic bisphenol E type epoxy compounds, diglycidyl ethers of alkylene oxide adducts of aromatic bisphenol A type, diglycidyl ethers of alkylene oxide adducts of aromatic bisphenol F type, diglycidyl ethers of alkylene oxide adducts of aromatic bisphenol E type, aromatic novolac type epoxy compounds, urethane-modified aromatic epoxy compounds, nitrogen-containing aromatic epoxy compounds, rubber-modified aromatic epoxy resins containing polybutadiene or nitrile butadiene rubber (NBR), etc.

[0062] Examples of oxetane compounds, which are cationically curable heteroatom-containing compounds having an oxetanyl group, include 3-ethyl-3-(alkoxymethyl)oxetanes such as 3-ethyl-3-(hexyloxymethyl)oxetane, 3-ethyl-3-(heptyloxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-(octyloxymethyl)oxetane, and 3-ethyl-3-(dodecyloxymethyl)oxetane.

[0063] The compound having a cationic curable functional group may be a bisphenol epoxy compound (III). Some bisphenol epoxy compounds (III) are the main components of commercially available curable epoxy compound compositions, but curing with a cationic polymerization initiator requires high temperatures and may cause cracking or coloring in the cured product. Examples of curable epoxy compound composition products containing bisphenol epoxy compounds (III) include Acryset (registered trademark) BR series manufactured by Nippon Shokubai Co., Ltd. and jER series manufactured by Mitsubishi Chemical Corporation. TM There is a series.

[0064] [ka] [In the formula, R 21 and R 22 are independently H, C1-6 Alkyl groups, halogenated C 1-6 R represents an alkyl group or a phenyl group. 21 and R 22 Let's get together and 3-10 may form a cycloalkyl group, r is an integer between 0 and 100.

[0065] r may be 0. The upper limit of r is preferably 50 or less, more preferably 10 or less, and even more preferably 5 or less or 3 or less.

[0066] The ratio of the compound having a cationic curable functional group and the thermal latent cationic polymerization initiator in the curable resin composition according to the present invention may be appropriately adjusted within a range in which the compound having a cationic curable functional group can be well cured, and for example, the mass ratio of the compound having a cationic curable functional group to 1 part by mass of the Lewis acid type cationic polymerization initiator (I) contained in the latent cationic polymerization initiator may be adjusted to about 50 or more and 200 or less. The ratio is preferably 60 or more, more preferably 80 or more, and is preferably 150 or less, more preferably 120 or less.

[0067] In addition, the curable resin composition according to the present invention may contain additives such as antistatic agents, curing agents, flame retardants, antibacterial agents, antioxidants, pigments, etc. It is also preferable to contain particles such as silica particles in order to improve the linear expansion coefficient and electrical properties.

[0068] In addition, the impact resistance of the cured product can be improved by blending rubber particles. Examples of rubber particles include acrylic rubber particles, silicone rubber particles, and fluororubber particles. The particle size of the rubber particles is not particularly limited, but for example, those having a volume-based average particle size of 0.05 μm or more and 2 μm or less can be used. The blending amount of the rubber particles in the curable resin composition is also not particularly limited, but can be, for example, 10 phr or more and 30 phr or less.

[0069] Hereinafter, the method for curing the curable resin composition and the method for producing the cured product according to the present invention will be described step by step, but the present invention is not limited to the specific examples below.

[0070] 1. Preparation of curable resin composition In this step, a compound having a cationic curable functional group and a thermal latent cationic polymerization initiator are mixed to prepare a curable resin composition. The thermal latent cationic polymerization initiator according to the present invention contains a Lewis acid type cationic polymerization initiator (I) and an amine compound.

[0071] 2. Molding process In this step, the curable resin composition prepared in the step 1 is molded. The molding method is not particularly limited and may be appropriately selected, and examples thereof include spin coating, solvent casting, dipping, spray coating, and dispenser methods. Spin coating is a method of coating a flat substrate with a liquid using centrifugal force, and this method can mold a liquid curable resin composition into a thin film. The solvent casting method is a method of pouring a liquid curable resin composition into a mold to form a mold. The dipping method is a method of immersing a mold or a substrate that serves as a core in a liquid curable resin composition to form a coating of the liquid curable resin composition on the substrate surface. The spray coating method is a method of spraying a liquid curable resin composition onto a substrate surface to form a coating of the liquid curable resin composition on the substrate surface. The dispenser method is a method of discharging a fixed amount of liquid curable resin composition onto a substrate from a device called a dispenser to form a coating of the liquid curable resin composition on the substrate surface.

[0072] 3.Curing process In this step, the curable resin composition is cured by heating. The curable resin composition according to the present invention does not cure at room temperature due to the action of the thermal latent cationic polymerization initiator according to the present invention, which is a polymerization catalyst. However, when heated, the thermal latent cationic polymerization initiator according to the present invention exerts its polymerization catalytic ability, and the composition cures.

[0073] The curing initiation temperature by the thermal latent cationic polymerization initiator according to the present invention is preferably 50°C or higher. If the curing initiation temperature is 50°C or higher, curing will hardly start at room temperature. The temperature is more preferably 60°C or higher or 80°C or higher, and even more preferably 100°C or higher. On the other hand, if the temperature is too high, there is a risk of the cured product decomposing, so the heating temperature is preferably 500°C or lower, more preferably 400°C or lower, even more preferably 300°C or lower, and even more preferably 200°C or lower.

[0074] It is believed that the thermal latent cationic polymerization initiator according to the present invention is dissociated from the amine compound by heating, and the polymerization reaction is initiated. It is unclear whether the amine compound dissociated from the thermal latent cationic polymerization initiator forms a complex with the thermal latent cationic polymerization initiator again after the polymerization reaction, or exists in a free state, but for example, an amine compound with a low boiling point such as ammonia may evaporate from the cured product and its concentration may become below the detection limit.

[0075] When a cured product cured using a thermal latent cationic polymerization initiator comes into contact with a metal, the cured product itself or the metal may discolor, especially under high temperature or high humidity conditions. The discolored metal portion may cause deterioration of characteristics or corrosion, leading to poor insulation. However, even when the cured product of the curable resin composition according to the present invention containing the thermal latent cationic polymerization initiator comes into contact with a metal, discoloration of the cured product of the curable resin composition and the metal is suppressed even under high temperature and high humidity conditions, probably due to the free amine compound present in an appropriate amount relative to the Lewis acid type cationic polymerization initiator (I).

[0076] The bonded structure according to the present invention includes a cured product of the curable resin composition and a metal, and the cured product and the metal are in contact with each other. As described above, the bonded structure according to the present invention has excellent corrosion resistance between the cured product and the metal.

[0077] The metal contained in the bonded body is not particularly limited, and examples thereof include copper, gold, silver, nickel, aluminum, and alloys of stainless steel, among which copper, silver, and nickel are preferred from the viewpoints of electrical conductivity, ease of handling, cost, and the like.

[0078] The shape of the metal is not particularly limited and may be appropriately selected, for example, spherical, plate-like, tubular, bulk, linear, sponge-like, etc. The plate-like shape may be a foil having a thickness of about 5 μm or more and 200 μm or less. The thickness is preferably 10 μm or more, and more preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 20 μm or less.

[0079] The shape of the cured product is not particularly limited, and may be, for example, spherical, plate-like, tubular, bulk, linear, or sponge-like. The thickness of the plate-like object may be appropriately selected, and may be, for example, 10 μm or more and 500 μm or less. The thickness is preferably 15 μm or more, more preferably 20 μm or more, and preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 50 μm.

[0080] Alternatively, a sheet of formed fibers such as carbon fibers may be impregnated with a solvent-containing curable resin composition to form a prepreg. The prepreg may be laminated with a metal foil and heated to cure the curable resin composition to form a metal-clad laminate.

[0081] In addition, the curable resin composition according to the present invention can also be used as an adhesive between metals or between a metal and other components, a conductive paste containing a conductive metal, an anisotropic conductive film (ACF) material, a sealant for circuit elements with exposed metal parts, and the like.

[0082] As described above, the combination of the Lewis acid type cationic polymerization initiator (I) and the amine compound can polymerize and harden the epoxy monomer well at a relatively low temperature. For example, with the conventional thermal latent cationic polymerization initiator, the bisphenol epoxy resin (III) could not be polymerized unless at a high temperature, or even if it could be polymerized, defects such as coloration and cracks could occur. However, with the combination of the Lewis acid type cationic polymerization initiator (I) and the amine compound according to the present invention, the bisphenol epoxy resin (III) can be polymerized and hardened at a relatively low temperature while suppressing defects.

[0083] The cured product produced by the method of the present invention can also be used as a protective layer for a printed wiring board. Specifically, the curable resin composition of the present invention is layered on a flexible and insulating plastic film such as polyester or polyimide so as to cover a conductor pattern of a flexible printed wiring board formed by a printing technique, and the curable resin composition is cured by heating and pressing to obtain a flexible printed wiring board provided with a protective layer.

[0084] The cured or semi-cured product of the present invention may be used as a resin film or a prepreg. For example, the curable resin composition of the present invention may be applied to a release film, cured or semi-cured by heating, and formed into a film to form a resin film or a prepreg. Semi-curing is, for example, B-staging.

[0085] It is believed that the combination of the Lewis acid type cationic polymerization initiator (I) according to the present invention and an amine compound polymerizes the epoxy monomer in a chain manner through the following reaction: In the following formula, R represents an unspecified hydrogen atom or an organic group, and multiple Rs may be the same or different.

[0086] [ka]

[0087] Since bisphenol epoxy resin (III) has two epoxy groups, its cured product may have a three-dimensional or higher-order structure. As a result, it is generally difficult to analyze the chemical structure of a polymer, but it is even more difficult to analyze the chemical structure of a cured product of bisphenol epoxy resin (III).

[0088] Since the present invention allows the epoxy monomer to be polymerized at a relatively low temperature, it is believed that at least a part of the Lewis acid type cationic polymerization initiator (I) remains in the cured product. On the other hand, since some amine compounds have a low boiling point, such as ammonia, the content of the amine compound in the cured product may be below the detection limit. EXAMPLES

[0089] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples, and it is possible to carry out the present invention by making appropriate modifications within the scope of the above and below-mentioned aims, and all of these modifications are included in the technical scope of the present invention.

[0090] Catalyst Production Example 1: Production of cationic polymerization initiator 1-1 Tris(pentafluorophenyl)borane (0.906 g, 1.770 mmol, hereafter abbreviated as "TPB") was added with 2 mol / L ammonia-2-propanol solution (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., containing 0.695 g, 1.770 mmol ammonia), and the mixture was stirred for 1 hour until it was dissolved.

[0091] Catalyst Production Example 2: Production of cationic polymerization initiator 1-2 A 2 mol / L ammonia-2-propanol solution (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., containing 0.834 g and 2.124 mmol of ammonia) was added to TPB (0.906 g, 1.770 mmol) and stirred for 1 hour until dissolved.

[0092] Catalyst Production Example 3: Production of Cationic Polymerization Initiator 1-3 A 2 mol / L ammonia-2-propanol solution (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., containing 0.903 g and 2.301 mmol of ammonia) was added to TPB (0.906 g, 1.770 mmol) and stirred for 1 hour until dissolved.

[0093] Catalyst Production Example 4: Production of Cationic Polymerization Initiator 1-4 A 2 mol / L ammonia-2-propanol solution (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., containing 1.042 g, 2.655 mmol of ammonia) was added to TPB (0.906 g, 1.770 mmol) and stirred for 1 hour until dissolved.

[0094] Catalyst Production Example 5: Production of Cationic Polymerization Initiator 1-5 A 2 mol / L ammonia-2-propanol solution (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., containing 1.390 g and 3.540 mmol of ammonia) was added to TPB (0.906 g, 1.770 mmol) and stirred for 1 hour until dissolved.

[0095] Catalyst Production Example 6: Production of Cationic Polymerization Initiator 1-6 A 2 mol / L ammonia-2-propanol solution (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., containing 2.084 g and 5.309 mmol of ammonia) was added to TPB (0.906 g, 1.770 mmol) and stirred for 1 hour until dissolved.

[0096] Catalyst Production Example 7: Production of cationic polymerization initiator 2-1 To TPB (10.556 g, 20.617 mmol), 2,2,6,6-tetramethyl-4-piperidine ester of 1,2,3,4-butanetetracarboxylic acid ("ADEKA STAB LA57" manufactured by ADEKA Corporation, 2.039 g, 2.577 mmol) and methoxycyclopentane (14,000 g) were added and stirred for 1 hour until dissolved.

[0097] Catalyst Production Example 8: Production of cationic polymerization initiator 2-2 To TPB (10.556 g, 20.617 mmol), 2,2,6,6-tetramethyl-4-piperidine ester of 1,2,3,4-butanetetracarboxylic acid having the following chemical structure ("ADEKA STAB LA57", manufactured by ADEKA Corporation, 2.854 g, 3.608 mmol) and methoxycyclopentane (14,000 g) were added and stirred for 1 hour until dissolved.

[0098] [ka]

[0099] Catalyst Production Example 9: Production of cationic polymerization initiator 2-3 To TPB (10.556 g, 20.617 mmol), 2,2,6,6-tetramethyl-4-piperidine ester of 1,2,3,4-butanetetracarboxylic acid ("ADEKA STAB LA57" manufactured by ADEKA Corporation, 3.262 g, 4.123 mmol) and methoxycyclopentane (14,000 g) were added and stirred for 1 hour until dissolved.

[0100] Catalyst Production Example 10: Production of cationic polymerization initiator 2-4 To TPB (10.556 g, 20.617 mmol), 2,2,6,6-tetramethyl-4-piperidine ester of 1,2,3,4-butanetetracarboxylic acid ("ADEKA STAB LA57" manufactured by ADEKA Corporation, 4.077 g, 5.154 mmol) and methoxycyclopentane (14,000 g) were added and stirred for 1 hour until dissolved.

[0101] Catalyst Production Example 11: Production of cationic polymerization initiator 2-5 To TPB (10.556 g, 20.617 mmol), 2,2,6,6-tetramethyl-4-piperidine ester of 1,2,3,4-butanetetracarboxylic acid ("ADEKA STAB LA57" manufactured by ADEKA Corporation, 4.485 g, 5.669 mmol) and methoxycyclopentane (14,000 g) were added and stirred for 1 hour until dissolved.

[0102] Catalyst Production Example 12: Production of cationic polymerization initiator 2-6 To TPB (10.556 g, 20.617 mmol), 2,2,6,6-tetramethyl-4-piperidine ester of 1,2,3,4-butanetetracarboxylic acid ("ADEKA STAB LA57" manufactured by ADEKA Corporation, 5.300 g, 6.700 mmol) and methoxycyclopentane (14.000 g) were added and stirred for 1 hour until dissolved.

[0103] Catalyst Production Example 13: Production of cationic polymerization initiator 2-7 To TPB (10.556 g, 20.617 mmol), 2,2,6,6-tetramethyl-4-piperidine ester of 1,2,3,4-butanetetracarboxylic acid (Adeka Corporation, "Adeka STAB LA57" Adeka Corporation, 8.154 g, 10.308 mmol) and methoxycyclopentane (14,000 g) were added and stirred for 1 hour until dissolved.

[0104] Catalyst Production Example 14: Production of cationic polymerization initiator 3-1 A hindered amine light stabilizer having the following chemical structure ("TINUVIN765" manufactured by BASF, 6.309 g, 12.370 mmol) and methoxycyclopentane (14,000 g) were added to TPB (10.556 g, 20.617 mmol) and stirred for 1 hour until dissolved.

[0105] [ka]

[0106] Test Example 1: Measurement of free amine value The free amine value of the prepared cationic polymerization initiator was measured. Bromophenol blue was dissolved in ethanol to prepare a 0.1% by mass ethanol solution, hereinafter referred to as BPB solution. A cationic polymerization initiator (1 g) and a BPB solution (0.2 mL) were added to a vial containing ethanol (10 mL), then the vial was capped and stirred for about 5 seconds. 0.5 mol / L hydrochloric acid (Kishida Chemical Co., Ltd.) was gradually added dropwise to the resulting solution. The solution color was confirmed to change from blue to green to yellow, and the end point was the point where it turned green. The amine compound that formed a complex with TPB did not react with hydrochloric acid, and the number of moles of hydrochloric acid required to be added was equivalent to the number of moles of amino groups contained in the free amine. The number of moles of amino groups contained in free amines per mole of boron in the cationic polymerization initiator subjected to measurement is taken as the free amine value, and is shown together with the molar ratio (N / B) of the amine compound to boron in the TPB used in producing the cationic polymerization initiator, in Tables 1 and 2. Note that when the color of the solution was green to yellow before the dropwise addition of hydrochloric acid, the free amine value was taken as 0. For comparison, the commercially available cationic polymerization initiator ("San-Aid SI-80L" manufactured by Sanshin Chemical Industry Co., Ltd.) does not contain any free amines in its structure. However, when it was measured in the same manner just to be sure, the color of the solution was yellow from the beginning.

[0107] [Table 1]

[0108] [Table 2]

[0109] Resin composition manufacturing example 1 A resin composition was obtained by uniformly mixing 1 part by mass of a cationic polymerization initiator with 100 parts by mass of an alicyclic epoxy compound ("Celloxide 2021P" manufactured by Daicel Corporation) for 5 minutes. For comparison, a resin composition was obtained in the same manner using a commercially available cationic polymerization initiator having the following chemical structure ("San-Aid SI-80L" manufactured by Sanshin Chemical Industry Co., Ltd.). Some of the resin compositions were cured at this point.

[0110] [ka]

[0111] Test example 2: Thermosetting test The resin composition, which was not yet cured at the time of mixing, was dropped onto a copper plate of 0.3×50×50 mm and spin-coated at 1000 rpm for 10 seconds. The copper plate coated with the resin composition was heated on a hot plate heated to 120° C. for 1 hour to be thermally cured.

[0112] Test example 3: Highly accelerated life test Using a highly accelerated life tester ("PC-242HS-E" manufactured by Hiranuma Seisakusho Co., Ltd.), each copper plate on which the resin composition had been thermally cured was held under harsh conditions of 100% RH and 120°C for 96 hours, after which the appearance was observed and evaluated according to the following criteria. The results are shown in Table 3.

[0113] [Table 3]

[0114] As shown in the results in Table 3, a resin composition containing a commercially available cationic polymerization initiator that does not contain an amine compound as a constituent component ("San-Aid SI-80L" manufactured by Sanshin Chemical Industry Co., Ltd.) exhibited thermosetting properties, but the cured product of the resin composition and the metal in contact with the cured product changed color from black to green under moist and hot conditions. In addition, the resin composition containing a cationic polymerization initiator with an excessively small free amine value relative to boron did not exhibit thermosetting properties and began to cure simply by mixing with an epoxy resin, whereas the resin composition containing a cationic polymerization initiator with an excessively large free amine value relative to boron did not cure even when heated. In contrast, a resin composition containing the cationic polymerization initiator according to the present invention, which has a free amine value relative to boron of 0.15 or more and 1.70 or less, exhibits thermosetting properties, that is, it does not harden at room temperature but hardens when heated, and the appearance of the cured product formed thereby does not change even when it comes into contact with metal under moist and hot conditions. Therefore, the cationic polymerization initiator composition and resin composition according to the present invention are very useful for forming a cured resin that can be cured in a controlled manner and that comes into contact with a metal, such as an insulating layer for a circuit board.

[0115] Catalyst Production Example 15: Production of cationic polymerization initiator 4-1 A hindered amine light stabilizer having the following chemical structure ("TINUVIN770" manufactured by BASF, 4.956 g, 10.309 mmol) and methoxycyclopentane (14,000 g) were added to TPB (10.556 g, 20.617 mmol) and stirred for 1 hour until dissolved.

[0116] [ka]

[0117] Catalyst Production Example 16: Production of cationic polymerization initiator 5-1 2-Ethyl-4-methylimidazole (Tokyo Chemical Industry Co., Ltd., 0.408 g, 3.711 mmol) having the following chemical structure, 2,2,6,6-tetramethyl-4-piperidine ester of 1,2,3,4-butanetetracarboxylic acid (ADEKA STAB LA57, ADEKA Corporation, 2.935 g, 3.711 mmol) and methoxycyclopentane (14,000 g) were added to TPB (10.556 g, 20.617 mmol) and stirred for 1 hour until dissolved.

[0118] [ka]

[0119] Catalyst Production Example 17: Production of cationic polymerization initiator 5-2 2-Ethyl-4-methylimidazole (Tokyo Chemical Industry Co., Ltd., 0.863 g, 7.832 mmol), 2,2,6,6-tetramethyl-4-piperidine ester of 1,2,3,4-butanetetracarboxylic acid (ADEKA STAB LA57, ADEKA Corporation, 2.935 g, 3.711 mmol) and methoxycyclopentane (14,000 g) were added to TPB (10.556 g, 20.617 mmol) and stirred for 1 hour until dissolved.

[0120] Catalyst Production Example 18: Production of cationic polymerization initiator 5-3 To TPB (10.556 g, 20.617 mmol), 2-ethyl-4-methylimidazole (Tokyo Chemical Industry Co., Ltd., 1.544 g, 14.019 mmol), 2,2,6,6-tetramethyl-4-piperidine ester of 1,2,3,4-butanetetracarboxylic acid (ADEKA STAB LA57, ADEKA Corporation, 2.935 g, 3.711 mmol) and methoxycyclopentane (14,000 g) were added and stirred for 1 hour until dissolved.

[0121] Resin composition manufacturing example 2 A resin composition was obtained in the same manner as in Resin Composition Production Example 1, except that 100 parts by mass of an aromatic epoxy compound ("YL980" manufactured by Adeka Corporation) was used instead of the alicyclic epoxy compound ("Celloxide 2021P" manufactured by Daicel Corporation). The thermosetting property of each resin composition was tested in the same manner as in Test Example 2, and the highly accelerated life of the cured product of each resin composition and the copper plate in contact with the cured product was tested in the same manner as in Test Example 3. The results are shown in Table 4.

[0122] [Table 4]

[0123] As shown in the results in Table 4, the resin composition containing the cationic polymerization initiator according to the present invention, which contains not only a hindered amine as an amine compound but also an imidazole compound in addition to the hindered amine, and has a free amine value relative to boron of 0.15 to 1.70, and an aromatic epoxy compound, does not cure at room temperature but cures upon heating, and the appearance of the cured product formed thereby does not change even when in contact with metal under moist and hot conditions, and the appearance of the metal in contact with the cured product also does not change. Therefore, the cationic polymerization initiator composition and resin composition according to the present invention are very useful for forming a cured resin that can be cured in a controlled manner and that comes into contact with a metal, such as an insulating layer for a circuit board.

[0124] Resin composition manufacturing example 3 The alicyclic epoxy compound or aromatic epoxy compound shown in Table 5 and the cationic polymerization initiator were mixed in the mass ratio shown in Table 6 to obtain a resin composition.

[0125] [Table 5]

[0126] [Table 6]

[0127] Test Example 4: Thermosetting test The uncured resin compositions were molded onto substrates and thermally cured under the conditions shown in Table 7, and the cured state and the appearance of the cured products were visually observed. The results are shown in Table 7. Also, photographs of the appearance of the cured products of Examples 1 and 2 and Comparative Examples 1 and 2 are shown in Figure 1.

[0128] [Table 7]

[0129] As shown in the results in Table 7 and FIG. 1, cracks and coloring were observed in the cured products of the resin compositions of Comparative Examples 1 to 3, which contained an alicyclic epoxy resin and a commercially available cationic polymerization initiator. In Comparative Examples 4 and 5, which contained an aromatic epoxy resin and a commercially available cationic polymerization initiator, poor curing occurred and no cured product was obtained. In contrast, in Examples 1 to 5 according to the present invention, the curing reaction proceeded sufficiently with heating at 120 to 160°C for 1 hour for both the alicyclic epoxy resin and the aromatic resin, and a cured product without defects such as coloration or cracks was obtained.

[0130] Test Example 5: Differential Scanning Calorimetry The heat generation characteristics of the curable resin composition were measured using a differential scanning calorimeter ("DSC 3500" manufactured by Netzsch Japan Co., Ltd.). The measurement conditions were a temperature rise rate of 10°C / min, and measurements were performed from 30°C to 250°C in a nitrogen atmosphere. The results are shown in Table 8.

[0131] [Table 8]

[0132] As shown in the results in Table 8, even with the commercially available initiator, the alicyclic epoxy compound could be polymerized (resin composition 7). However, in the case of aromatic epoxy compounds, when using commercially available initiators, the curing reaction did not proceed at all (resin composition 9), or even if it did proceed, the amount of heat generated was small and curing was insufficient (resin composition 8). In contrast, in the case of resin compositions 1 to 6 according to the present invention, heat generation accompanying the curing reaction was observed for both the alicyclic epoxy compound and the aromatic epoxy compound, and since the amount of heat generated was large, it was found that curing had progressed sufficiently.

[0133] Test Example 6: Dynamic Viscoelasticity Measurement The storage modulus, loss modulus and tan δ of the cured material were measured using a dynamic viscoelasticity measuring device ("DMA RSA-G2" manufactured by TA Instruments Japan). The measurement conditions were three-point bending, heating rate of 5°C / min, measurement from 30°C to 250°C, normal load of 10g and sensitivity of 2g. The sample size was 5mm x 20mm x thickness 2mm. The results are shown in Table 9.

[0134] [Table 9]

[0135] Dynamic elastic modulus includes storage elastic modulus (Pa) and loss elastic modulus (Pa), storage elastic modulus is the component of energy generated by external force and strain that is stored inside the object, while loss elastic modulus is the component that diffuses to the outside. Tan δ is called the loss factor and is expressed as loss elastic modulus / storage elastic modulus, and the larger the value, the higher the viscosity and the easier it is to diffuse energy generated by strain to the outside, making it more resistant to impact. As shown in the results in Table 9, the cured products of Examples 3 to 5 according to the present invention not only have a high Tg of 100°C or more, but also exhibit a high tan δ compared to the cured product of Comparative Example 3 using a commercially available initiator. This indicates that the cured products are capable of diffusing external strain and have high impact resistance.

Claims

1. The present invention comprises a Lewis acid type cationic polymerization initiator represented by the following formula (I) and an amine compound, the Lewis acid type cationic polymerization initiator and a part of the amine compound form a complex, the remainder of the amine compound is present free from the Lewis acid type cationic polymerization initiator, A thermally latent cationic polymerization initiator, characterized in that a molar ratio of amino groups contained in the free amine compound to 1 mole of boron atoms contained in the Lewis acid type cationic polymerization initiator is 0.15 or more and 1.70 or less. 【Chemistry 1】 [In the formula, F represents a fluoro group; R 1 represents a hydrocarbon group which may have a substituent, l represents an integer of 1 to 5, m represents an integer of 1 to 3, n represents an integer of 0 to 2, m+n=3, When n is 2, two R 1 may be the same or different.

2. The thermal latent cationic polymerization initiator according to claim 1, further comprising a solvent.

3. 2. The thermal latent cationic polymerization initiator according to claim 1, wherein the amine compound is a hindered amine compound.

4. 2. The thermal latent cationic polymerization initiator according to claim 1, wherein the amine compound is an imidazole compound and a hindered amine compound.

5. 2. The thermal latent cationic polymerization initiator according to claim 1, wherein the Lewis acid type cationic polymerization initiator represented by formula (I) is tris(pentafluorophenyl)borane.

6. A curable resin composition comprising a compound having a cationic curable functional group and the thermal latent cationic polymerization initiator according to any one of claims 1 to 5.

7. The curable resin composition according to claim 6, wherein the compound having a cationically curable functional group is at least one selected from the group consisting of an alicyclic epoxy compound, a hydrogenated epoxy compound, an aromatic epoxy compound, and an oxetane compound.

8. A cured product of the curable resin composition according to claim 6 and a metal, A bonded body, characterized in that the cured product and the metal are in contact with each other.

9. A printed wiring board comprising an insulating layer comprising the cured product of the curable resin composition according to claim 6, and a conductor layer on one or both sides of the insulating layer.

Citation Information

Patent Citations

  • Curing catalysts, compositions, electronic devices and related methods

    JP2008544067A

  • Curable resin composition, cured product of the same, and optical material

    JP2014152194A

  • Composition containing triaryl boron compound

    JP2019218267A

  • Thermosetting epoxy resin composition, laminate for circuit board, metal-based circuit board, and power module

    JP2021066890A

  • Composition usable as heat-latent polymerization initiator

    WO2012036164A1